Stepwise crystallographic visualization of dynamic guest binding in a nanoporous framework. Issue 4 (23rd February 2017) - Brunet, Gabriel; Safin, Damir A.; Aghaji, Mohammad Z.; Robeyns, Koen; Korobkov, Ilia; Woo, Tom K.; Murugesu, Muralee
Abstract : The dynamic uptake behaviour of a gaseous guest has been observed crystallographically, yielding a unique and ever-changing set of host–guest interactions that will drive the improvement of high-capacity iodine capture materials. Abstract : Binding sites are at the heart of all host–guest systems, whether biological or chemical. When considering binding sites that form covalent bonds with the guest, we generally envision a single, highly specific binding motif. Through single-crystal X-ray crystallography, the dynamic binding of a guest that displays a variety of covalent binding motifs in a single site of adsorption is directly observed for the first time. The stepwise crystallographic visualization of the incorporation of I2 within a porous MOF is presented, wherein the preferred binding motifs throughout the uptake process are identified. The guest I2 molecules initially bind with terminal iodide atoms of the framework to form [I4 ] 2− units. However, as the adsorption progresses, the I2 molecules are observed to form less energetically favorable I3 − groups with the same framework iodide atoms, thereby allowing for more guest molecules to be chemisorbed. At near saturation, even more binding motifs are observed in the same pores, including both physisorbed and chemisorbed guest molecules. Herein, we present the successful identification of a unique set of host–guest interactions which will drive the improvement of high capacity iodine capture materials.